Microbial-assisted soil chromium immobilization through zinc and iron-enriched rice husk biochar - Batool, Masooma; Rahman, Shafeeq ur; Ali, Muhammad; Nadeem, Faisal; Ashraf, Muhammad Nadeem; Harris, Muhammad; Du, Zhenjie; Khan, Waqas-ud-Din (Frontiers in Microbiology, 2022)
Soil chromium toxicity usually caused by the tannery effluent compromises the environment and causes serious health hazards. The microbial role in strengthening biochar for its soil chromium immobilization remains largely unknown. Hence, this study evaluated the effectiveness of zinc and iron-enriched rice husk biochar (ZnBC and FeBC) with microbial combinations to facilitate the chromium immobilization in sandy loam soil. We performed morphological and molecular characterization of fungal [Trichoderma harzianum (F1), Trichoderma viride (F2)] and bacterial [Pseudomonas fluorescence (B1), Bacillus subtilis (B2)] species before their application as soil ameliorants. There were twenty-five treatments having ZnBC and FeBC @ 1.5 and 3% inoculated with bacterial and fungal isolates parallel to wastewater in triplicates. The soil analyses were conducted in three intervals each after 20, 30, and 40 days. The combination of FeBC 3%+F2 reduced the soil DTPA-extractable chromium by 96.8% after 40 days of incubation (DAI) relative to wastewater. Similarly, 92.81% reduction in chromium concentration was achieved through ZnBC 3%+B1 after 40 DAI compared to wastewater. Under the respective treatments, soil Cr(VI) retention trend increased with time such as 40 > 30 > 20 DAI. Langmuir adsorption isotherm verified the highest chromium adsorption capacity (41.6 mg g−1) with FeBC 3% at 40 DAI. Likewise, principal component analysis (PCA) and heat map disclosed electrical conductivity-chromium positive, while cation exchange capacity-chromium and pH-organic matter negative correlations. PCA suggested the ZnBC-bacterial while FeBC-fungal combinations as effective Cr(VI) immobilizers with >70% data variance at 40 DAI. Overall, the study showed that microbes + ZnBC/FeBC resulted in low pH, high OM, and CEC, which ultimately played a role in maximum Cr(VI) adsorption from wastewater applied to the soil. The study also revealed the interrelation and alternations in soil dynamics with pollution control treatments. Based on primitive soil characteristics such as soil metal concentration, its acidity, and alkalinity, the selection criteria can be set for treatments application to regulate the soil properties. Additionally, FeBC with Trichoderma viride should be tested on the field scale to remediate the Cr(VI) toxicity.